Prevalence of Cognitive Impairment and Associated Factors in Diabetic Patients Attending a Rural Health Facility in Goa, India - Vedika Gad; Aparna Rajendran; Jagadish Cacodcar (National Journal of Community Medicine)
Introduction: Diabetes prevalence is rising globally, projected to reach 643 million by 2030, with India's rate surpassing the global average. Cognitive impairment (CI) is a common, yet underdiagnosed complication.